A Study On Puerperal Events And Postpartum Reproductive Performance In Gir Cows - Ramakrishnan, Ammu; Dhami, A.J. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
This investigation was undertaken on 24 normal parturient Gir cows of 2nd to 4th parity on an organized farm to evaluate the puerperal events and postpartum fertility with and without use of estrus induction / synchronization protocols (viz., CIDR, Ovsynch and Cosynch) around day 90- 92 postpartum in anoestrus/suboestrus cows. Per rectal palpation was carried out periodically during early postpartum period to monitor ovarian changes and uterine involution, and around day 70- 90 at 10 days intervals to confirm anoestrus/suboestrus condition. The plasma progesterone levels were estimated by RIA at 10 days interval from calving till 140 days postpartum. The birth weight of calf, time required for expulsion of fetal membranes and weight of expelled fetal membranes were 19.08 ± 0.84 kg, 4.67 ± 0.46 hrs and 3.06 ± 0.19 kg, respectively. Complete uterine involution was noted in Gir cows by mean interval of 36.54 ± 0.68 (range 31-42) days postpartum. The interval for occurrence of first estrus postpartum clinically and through plasma progesterone profile was 94.29 ± 2.24 (range 70-101) and 65.42 ± 5.77 (range 20-101) days, respectively (P<0.05). The first service and overall conception rates obtained were 41.66 per cent (10/24) and 87.50 per cent (21/24) within 150 days postpartum. The fertility response to all three estrus synchronization treatments used in anoestrus/suboestrus cows was at par with that of the normal cyclic cows in the same herd.